University Support for Students during Coronavirus Outbreak Pandemic from Malaysian Experience - Ismi Arif Ismail; Steven Eric Krauss; Habibah Ab Jalil; Abd Rahman Ahmad; Mohd Shahir Shamsir Omar (Communications of International Proceedings, 2020)
The speed at which COVID-19 has altered global education systems is unprecedented. In an effort to enhance support systems during the prolonged crisis period, and to better prepare Higher Learning Institutions (HLIs) for similar future events, this survey was conducted to capture the state of Universiti Tun Hussein Onn Malaysia (UTHM) students’ well-being in the context of university support during the COVID-19 pandemic. The main objective of this paper is to help the university to formulate effective policies to respond to the coronavirus (COVID 19) outbreak they can further improve on communication with students to ensure the latter is updated frequently. Considering the survey findings, recommendations are made for administrators, lecturers, and students to address student well-being and continuity of learning during the coronavirus pandemic situation.
Keywords: Higher Learning Institutions; student learning; learning resources; COVID-19